Bifunctional catalyst based on interlayer confinement effect of hydrotalcite nanoreactor as well as preparation method and application of bifunctional catalyst
By introducing catalytically active metals and chloride ions between the hydrotalcite nanoreactor layers, a dual-function catalyst was constructed, which solved the problems of low activity and poor selectivity of traditional catalysts, and achieved efficient catalysis in the hydrogenation and dechlorination reaction of organic chlorides Performance and stability.
Patent Information
- Application Number
- CN202411514431.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional catalysts have limited large-scale industrial applications due to low activity, poor selectivity and short operating cycles, especially in the hydrogenation and dechlorination reactions of organic chlorides.
Using a dual-function catalyst based on the interlayer confined domain effect of hydrotalcite nanoreactor, by introducing catalytic activity metals and chloride ions into the hydrotalcite layer, the interlayer confined domain effect is used to construct the synergistic effect of active metals and chloride ions and atomic level. Dispersed catalyst.
It has achieved large-scale industrial applications with excellent activity and ethylene selectivity under mild reaction conditions, with outstanding catalytic performance, easy recycling and reuse, and good stability.
Smart Images

Figure CN119386857A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor, a preparation method thereof, and application of the bifunctional catalyst in hydrogenation and dechlorination reactions of organic chlorides. Background Art
[0002] With the rapid development of urbanization and industrialization, the release of chlorinated organic compounds by human activities continues to increase, causing pollution to the atmosphere, soil, and water resources, seriously endangering human health. Therefore, it is urgent to develop efficient organic chlorinated compound conversion technology. At present, the most commonly used methods in industry are physical adsorption, biodegradation, and chemical reduction. Among them, chemical reduction can convert chlorinated organic compounds into high value-added products. It is a simple operation, no secondary pollution, and high atom economy approach, and has good application prospects in the treatment of chlorinated pollutants. However, traditional catalysts are limited in large-scale industrial applications due to problems such as low activity, poor selectivity, and short operating cycle.
[0003] Nanoreactors have received extensive attention in terms of catalytic performance enhancement due to their spatial confinement effect, which enables the transition state produced by catalytic reactions to be regulated at the molecular / atomic scale, thereby achieving synergy, tandem, and coupling. However, research on the catalytic reaction process in nanoreactors is still unclear, such as the controllable directional growth and stable dispersion of multifunctional groups (metal complexes, metal nanoparticles) in nanoreactors. Therefore, the rational design and precise construction of nanoreactors are crucial to improving catalytic reaction performance.
[0004] Layered double hydroxides (LDHs) are multifunctional anionic layered compounds, commonly known as hydrotalcite. Due to the interlayer confinement effect of LDHs and the exchangeability of anions, they are used as nanoreactors, providing an innovative platform for the preparation of new and efficient catalysts. Summary of the invention
[0005] In view of this, in order to solve the technical problems that traditional catalysts are limited in large-scale industrial applications due to low activity, poor selectivity, short operating cycle, etc., in the first aspect, the present invention provides a bifunctional catalyst based on the interlayer confinement effect of hydrotalcite nanoreactors, which utilizes the interlayer anion exchangeability of LDHs nanoreactors to introduce catalytically active metals and chloride ions into the interlayers, and through the interlayer confinement effect, constructs a B catalyst with synergistic action of active metals and chloride ions and atomic-level dispersion. 12 H 12 -M1-Cl@X 2+ Y 3+-LDHs bifunctional catalyst. It is applied to the hydrogenation and dechlorination of organic chlorides, has excellent activity and ethylene selectivity, outstanding catalytic performance, easy recovery and reuse, and good stability.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The bifunctional catalyst based on the interlayer confinement effect of hydrotalcite nanoreactor is denoted as B 12 H 12 -M1-Cl@X 2+ Y 3 + -LDHs, where M is a catalytically active and atomically dispersed metal, B 12 H 12 is the interlayer anion of the anchored active metal M; Cl is the interlayer anion adjacent to M1; X 2+ Y 3+ -LDHs is a hydrotalcite nanoreactor, wherein X is a divalent metal, Y is a high-valent metal, 2+ Y 3+ -LDHs interlayer spacing is 0.80-0.85nm, and the active metal M is in X 2+ Y 3+ -LDHs are dispersed atomically and stably between layers and are bound by adjacent Cl - The synergistic effect forms a bifunctional M-Cl active site.
[0008] Preferably, M is at least one of Pd, Pt, Rh, and Ru, preferably at least one of Pd and Pt; preferably, the loading amount of M is 0.01 to 1.0 wt.%, more preferably 0.01 to 0.2 wt.%, wherein the loading amount of M is a percentage of the bifunctional catalyst.
[0009] Preferably, X is one or two of Mg, Zn, Cu and Ni; Y is one of Al, Fe, Cr, Ti and Zr.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor, comprising the following steps:
[0011] Step A, dissolving a divalent metal salt and a high-valent metal salt in boiling water to prepare a mixed salt solution I; dissolving an alkali in boiling water to prepare an alkali solution; dissolving a boron cluster compound in boiling water to prepare a salt solution II;
[0012] Under an inert atmosphere, the mixed salt solution I and the alkaline solution are added to the salt solution II, and the pH of the solution is maintained at 8.5 to perform a crystallization reaction. After the crystallization is completed, the boron clusters are located in the layers and between the layers. 12 H12 / X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs;
[0013] Step B: B obtained in step A 12 H 12 / X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in boiling water, and an oxidizing acid solution was added dropwise under an inert atmosphere. After stirring and centrifugation, the supernatant was poured off, and then dried to obtain a X-type product in which the boron clusters were located only between the layers. 2+ Y 3 + -B 12 H 12 2- -Cl - -LDHs precursor;
[0014] Step C: inserting the boron cluster obtained in step B into the X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs precursor is evenly dispersed in boiling water, and a metal salt solution with catalytic activity is added dropwise under an inert atmosphere. After stirring and centrifugation to remove the supernatant, the hydrotalcite nanoreactor with interlayer confinement effect and atomic-level dispersion is obtained after drying. 12 H 12 -M1-Cl@X 2+ Y 3+ -LDHs bifunctional catalysts.
[0015] Preferably, in step A, the total amount of metal ions in the divalent metal salt and the high-valent metal salt is 8 to 24 mmol·L -1 , preferably the molar ratio of the divalent metal salt to the high-valent metal salt is 2 to 5;
[0016] In step A, the concentration of the alkaline solution is 16 to 48 mmol·L -1 , the concentration of salt solution II is 8~24mmol·L -1 .
[0017] Preferably, in step A, the crystallization reaction conditions are: crystallization at 70-90° C. for 72-120 h, preferably 84-100 h.
[0018] Preferably, in step A, the base is preferably one of NaOH and KOH; the boron cluster is preferably CsB 12 H 12 , Na2B 12 H 12 、K2B 12 H 12 Preferably, the mixed salt solution I and the alkaline solution are simultaneously added dropwise to the salt solution II;
[0019] The boiled water in step A, step B and step C is preferably deionized water to remove the interference of carbon dioxide;
[0020] The inert atmosphere in step A, step B and step C is preferably one of N2, Ar and He that does not contain CO2.
[0021] Preferably, in step B, the oxidizing acid is preferably one of HNO3, HNO2, HClO4, HClO2, and HClO, and more preferably one of HNO3 and HNO2; the concentration of the oxidizing acid solution is 1 to 5 mmol / L, preferably 1 to 2 mmol / L, and the amount used is 1 to 10 mL, preferably 1 to 5 mL.
[0022] Preferably, the drying conditions in step A, step B and step C are preferably vacuum freeze drying at 0 to -60°C, preferably -50°C, and the pressure is preferably 0 MPa.
[0023] In a third aspect, the present invention provides the use of the above-mentioned bifunctional catalyst based on the interlayer confinement effect of the hydrotalcite nanoreactor in the hydrogenation and dechlorination reactions of organic chlorides.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The bifunctional catalyst based on the interlayer confinement effect of the hydrotalcite nanoreactor provided by the present invention utilizes the interlayer confinement effect and composition controllability of the hydrotalcite nanoreactor and adopts the interlayer ion exchange method to combine the catalytically active metal with the chloride ion and the reducible B 12 H 12 2- Introduce interlayer and use B 12 H 12 2- The active metal species are anchored and reduced, their agglomeration growth is inhibited, and through the interlayer confinement effect, a B-type structure with synergistic action of active metals and chloride ions and atomic-level dispersion is constructed. 12 H 12 -M1-Cl@X 2+ Y 3+ -LDHs bifunctional catalyst. The structural features are: X 2+ Y 3+-LDHs nanoreactor interlayer spacing is 0.80-0.85nm, B 12 H 12 2- The active metal species are anchored between the layers, making them atomically dispersed and metallic, and through their interaction with adjacent Cl - The synergistic effect formed a bifunctional M-Cl catalytic active site, achieving a synergistic enhancement of conversion rate and selectivity under mild reaction conditions. At the same time, the interlayer confinement effect of the hydrotalcite nanoreactor effectively inhibited the agglomeration of active metals during the preparation and reaction process, resulting in the catalyst having good structural stability.
[0026] The bifunctional catalyst provided by the present invention is used in the hydrogenation and dechlorination reactions of organic chlorides, specifically in the hydrogenation and dechlorination reactions of organic chlorides in important fine and environmental chemical processes, and has excellent activity and ethylene selectivity, outstanding catalytic performance, easy recovery and reuse, and good stability.
[0027] The preparation method of the bifunctional catalyst provided by the present invention utilizes the interlayer confinement effect and composition controllability of the hydrotalcite nanoreactor and adopts the interlayer ion exchange method to convert the catalytically active Cl - Ions and reducible B 12 H 12 2- Introduced into the hydrotalcite interlayer, using B 12 H 12 2- Anchoring and reducing active metal species, inhibiting their agglomeration growth, and making them confined within the layer space with adjacent Cl - Synergistically, forming B 12 H 12 -M1-Cl@X 2+ Y 3+ -LDHs bifunctional catalyst. The preparation conditions are mild, no surfactant is required during the preparation process, and the process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 B prepared in Example 1 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -HRTEM and Mapping photos of LDHs bifunctional catalyst;
[0029] Figure 2 B prepared in Example 1 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -XRD spectrum of LDHs bifunctional catalyst;
[0030] Figure 3 B prepared in Example 1 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalyst in the selective dechlorination of trichloroethylene (A) 140℃, (B) 115℃ conversion and selectivity bar graph;
[0031] Figure 4 B prepared in Example 1 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalyst for the selective dechlorination of trichloroethylene. DETAILED DESCRIPTION
[0032] The above technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.
[0033] Example 1
[0034] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to a concentration of 12 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 96 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was poured off, and then vacuum freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain boron clusters located simultaneously in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs.
[0035] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl- -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 2 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the Mg- ... 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0036] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain a B nanoreactor with interlayer confinement effect and atomic-level dispersion. 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalysts.
[0037] like Figure 1 As shown, B prepared from Example 1 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalyst, the HRTEM and mapping images showed that Pd was atomically dispersed without obvious aggregated particles. - The active ingredients are evenly distributed.
[0038] like Figure 2 As shown in the figure, it is observed that the characteristic diffraction peak of the hydrotalcite (003) is obviously shifted to a low angle. The interlayer spacing calculated according to the Bragg equation is 0.83nm, which is consistent with the traditional Mg 2+ Al 3+ -LDHs (0.78 nm), indicating that the active metal Pd was successfully inserted into the interlayer of hydrotalcite.
[0039] The catalyst prepared in Example 1 above was used in the selective dechlorination reaction of trichloroethylene:
[0040] Weigh 0.3g of the above catalyst and 2g of quartz sand into a fixed bed reactor, introduce a mixed gas of H2 / C2HCl3=3 / 1, N2 as the balance gas and a total flow rate of 20-80mL / min, and test at 60-150°C. The reactor outlet gas is detected by gas chromatograph. The results are shown in Table 1. Figure 3 and Figure 4 .
[0041] like Figure 3 As shown, when the reaction temperature is 140°C, the trichloroethylene conversion rate of the catalyst reaches 98% and the ethylene selectivity is 96.2%; when the reaction temperature is 115°C, the trichloroethylene conversion rate is 98% and the vinyl chloride selectivity is 86%. Compared with the catalysts obtained in the following comparative examples 1-4, the catalyst can selectively dechlorinate, and the catalytic performance is significantly improved.
[0042] like Figure 4 As shown, after 7 h, the conversion rate (92%) and selectivity (94%±2%) of the catalyst did not decrease significantly, indicating that it has good long-term stability.
[0043] Compared with the catalyst reported in Gas-phase hydrodechlorination of trichloroethylene over Pd / NiMgAl mixed oxide catalysts, Applied Catalysis B: Environmental. 2012, 117 (300°C @ conversion rate 92%, ethylene selectivity 80%), while maintaining a high conversion rate, the reaction temperature is greatly reduced and the ethylene selectivity is significantly improved, which has a significant technical effect compared with the catalyst reported in the literature.
[0044] Example 2
[0045] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 3 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to a concentration of 12 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 96 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was poured off, and then vacuum freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain boron clusters located simultaneously in the layers and between the layers. 12 H12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs.
[0046] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 2 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the Mg- ... 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0047] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1 The Na2PtCl6 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain a hydrotalcite nanoreactor with interlayer confinement effect and atomic-level dispersion B 12 H 12 -Pt-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalysts.
[0048] The catalyst prepared in Example 2 above was used in the selective dechlorination reaction of trichloroethylene:
[0049] 0.3 g of the above catalyst and 2 g of quartz sand were weighed and loaded into a fixed bed reactor, and a mixed gas of H2 / C2HCl3=3 / 1 and N2 as the balance gas with a total flow rate of 20-80 mL / min was introduced. The test was carried out in the range of 60-150°C. The reactor outlet gas was detected by gas chromatograph. At 140°C, the conversion rate and selectivity were 97% and 94.7%; at 115°C, the trichloroethylene conversion rate was 95% and the vinyl chloride selectivity was 83%.
[0050] Example 3
[0051] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 5 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to a concentration of 12 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 84 hours; after the crystallization was completed, the solution was washed, centrifuged and the supernatant was poured off, and then freeze-dried in a vacuum at a temperature of -50°C and a pressure of 0 MPa to obtain boron clusters located simultaneously in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs.
[0052] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 2 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the Mg- ... 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0053] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain the B nanoreactor with interlayer confinement effect and atomic-level dispersion. 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalysts.
[0054] The catalyst prepared in Example 3 above was used in the selective dechlorination reaction of trichloroethylene:
[0055] 0.3g of the above catalyst and 2g of quartz sand were weighed and loaded into a fixed bed reactor, and a mixed gas of H2 / C2HCl3=3 / 1 was introduced, with N2 as the balance gas and a total flow rate of 20-80mL / min, and the test was carried out in the range of 60-150°C, and the reactor outlet gas was detected by a gas chromatograph. When the reaction temperature was 140°C, the trichloroethylene conversion rate of the catalyst reached 95% and the ethylene selectivity was 92%; when the reaction temperature was 115°C, the trichloroethylene conversion rate was 93% and the vinyl chloride selectivity was 90%.
[0056] Example 4
[0057] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 24 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 48 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to a concentration of 24 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 100 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was poured off, and then freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain the boron clusters located in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H12 2- -Cl - -LDHs.
[0058] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 5 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the Mg- ... 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0059] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain the B nanoreactor with interlayer confinement effect and atomic-level dispersion. 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalysts.
[0060] The catalyst prepared in Example 4 above was used in the selective dechlorination reaction of trichloroethylene:
[0061] 0.3g of the above catalyst and 2g of quartz sand were weighed and loaded into a fixed bed reactor, and a mixed gas of H2 / C2HCl3=3 / 1 was introduced, with N2 as the balance gas and a total flow rate of 20-80mL / min, and the test was carried out in the range of 60-150°C, and the reactor outlet gas was detected by a gas chromatograph. When the reaction temperature was 140°C, the trichloroethylene conversion rate of the catalyst reached 90% and the ethylene selectivity was 97%; when the reaction temperature was 115°C, the trichloroethylene conversion rate was 93% and the vinyl chloride selectivity was 88%.
[0062] Example 5
[0063] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 8 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 16 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to a concentration of 8 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 96 hours; after the crystallization was completed, the solution was washed, centrifuged and the supernatant was poured off, and then freeze-dried in a vacuum at a temperature of -50°C and a pressure of 0 MPa to obtain the boron clusters located in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs.
[0064] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 1 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the MgO2 solution was obtained after freeze drying at -50 °C and 0 MPa. 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0065] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain a B nanoreactor with interlayer confinement effect and atomic-level dispersion. 12 H 12 -Pd-Cl@Mg 2+ Al 3+ -LDHs bifunctional catalysts.
[0066] The catalyst prepared in Example 5 above was used in the selective dechlorination reaction of trichloroethylene:
[0067] 0.3g of the above catalyst and 2g of quartz sand were weighed and loaded into a fixed bed reactor, and a mixed gas of H2 / C2HCl3=3 / 1 was introduced, with N2 as the balance gas and a total flow rate of 20-80mL / min, and the test was carried out in the range of 60-150°C, and the reactor outlet gas was detected by a gas chromatograph. When the reaction temperature was 140°C, the trichloroethylene conversion rate of the catalyst reached 90% and the ethylene selectivity was 98%; when the reaction temperature was 115°C, the trichloroethylene conversion rate was 95% and the vinyl chloride selectivity was 80%.
[0068] Comparative Example 1
[0069] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to 100 mL of deionized water, and the pH of the solution was maintained between 8.5, and crystallized at 80°C for 96 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was decanted, and then vacuum freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain chloride ion intercalated Mg 2+ Al 3+ -Cl - -LDHs.
[0070] B. The Mg obtained in step A 2+ Al 3+ -Cl - -LDHs were evenly dispersed in 10 mL of boiling water, and 10 mL of 2 mmol CsB was added dropwise under N2 atmosphere. 12 H 12 The solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain the boron cluster loaded on the layer plate. 12 H 12 / Mg 2+ Al 3+ -Cl- -LDHs;
[0071] C. Load the boron cluster obtained in step B onto the B 12 H 12 / Mg 2+ Al 3+ -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 200 μL of 50 mmol·L was added dropwise under N2 atmosphere. -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain hydrotalcite-loaded B 12 H 12 -Pd / Mg 2+ Al 3+ -Cl - -LDHs catalysts are characterized by the Pd atoms being located outside the layer and the Cl atoms being located between the layers. - The ions have no synergistic effect.
[0072] The catalyst prepared in Comparative Example 1 was used in the selective dechlorination reaction of trichloroethylene:
[0073] Weigh 0.3g of the above catalyst and 2g of quartz sand into a fixed bed reactor, introduce a mixed gas of H2 / C2HCl3=3 / 1, N2 as the balance gas and a total flow rate of 20-80mL / min, and test at 60-150°C. The reactor outlet gas is detected by gas chromatograph. The results are shown in Table 1. Figure 3 Since the Pd atoms in the layer plate are not connected to the interlayer Cl - Ion synergy, when the reaction temperature is 140°C, the trichloroethylene conversion rate of the catalyst reaches 72% and the ethylene selectivity is 63%. When the reaction temperature is 115°C, the trichloroethylene conversion rate of the catalyst reaches 59% and the vinyl chloride selectivity is 15%, which are much lower than those of Example 1-5, indicating that Example 1-5 has significant technical effects compared with Comparative Example 1.
[0074] Comparative Example 2
[0075] A. Dissolve magnesium carbonate and aluminum carbonate in 100 mL of deionized water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of deionized water to a concentration of 24 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of deionized water to make a concentration of 12 mmol·L -1Salt solution II. Add the mixed salt solution I and the alkaline solution to the salt solution II at the same time, and keep the pH of the solution between 8.5, and crystallize at 80°C for 96 hours; after the crystallization is completed, wash, centrifuge and pour off the supernatant, and then freeze-dry at a temperature of -50°C and a pressure of 0MPa to obtain boron clusters located in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -CO3 2- -LDHs.
[0076] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -CO3 2- -LDHs were evenly dispersed in 50 mL of deionized water, and 2 mL of 2 mmol HNO3 solution was added dropwise. After stirring, the supernatant was centrifuged and the supernatant was poured off. After vacuum freeze drying at -50 °C and 0 MPa, the Mg- ... 2+ Al 3+ -B 12 H 12 2- -CO3 2- -LDHs;
[0077] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al 3+ -B 12 H 12 2- -CO3 2- -LDHs precursor was evenly dispersed in 50mL of boiling water, and 200μL of 50mmol·L -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain the B hydrotalcite nanoreactor with interlayer confinement effect and atomic-level dispersion. 12 H 12 -Pd@Mg 2+ Al 3+ -LDHs catalyst, characterized in that the interlayer ion is CO3 which has no dechlorination activity 2- , and has no synergistic effect with the interlayer Pd atoms.
[0078] The catalyst prepared in Comparative Example 2 was used in the selective dechlorination reaction of trichloroethylene:
[0079] Weigh 0.3g of the above catalyst and 2g of quartz sand into a fixed bed reactor, introduce a mixed gas of H2 / C2HCl3=3 / 1, N2 as the balance gas and a total flow rate of 20-80mL / min, and test at 60-150°C. The reactor outlet gas is detected by gas chromatograph. The results are shown in Table 1. Figure 3 Since the hydrotalcite interlayers are carbonate groups, they do not have dechlorination properties and cannot cooperate with the interlayer Pd species. When the reaction temperature is 140°C, the trichloroethylene conversion rate of the catalyst reaches 89% and the ethylene selectivity is 80%. When the reaction temperature is 115°C, the trichloroethylene conversion rate of the catalyst reaches 80% and the vinyl chloride selectivity is 23%. Compared with Examples 1-5, the conversion rate and selectivity are much lower than those of Examples 1-5, indicating that Examples 1-5 have significant technical effects compared with Comparative Example 2.
[0080] Comparative Example 3
[0081] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare a mixed salt solution. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; under N2 atmosphere, the mixed salt solution and the alkaline solution were simultaneously added dropwise to a flask containing 100 mL of boiling water, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 48 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was decanted, and then freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain a Cl - Mg 2+ Al 3+ -Cl - -LDHs catalyst, characterized by having catalytically active Cl - , but there is no Pd, no Pd and Cl - Synergy.
[0082] The catalyst prepared in Comparative Example 3 was used in the selective dechlorination reaction of trichloroethylene:
[0083] Weigh 0.3g of the above catalyst and 2g of quartz sand into a fixed bed reactor, introduce a gas mixture of H2 / C2HCl3=3 / 1, N2 as the balance gas and a total flow rate of 20-80mL / min, and test at 60-150℃. The reactor outlet gas is detected by gas chromatograph. -, without coordination with Pd, when the reaction temperature is 140°C, the trichloroethylene conversion rate of the catalyst reaches 62% and the ethylene selectivity is 65%. When the reaction temperature is 115°C, the trichloroethylene conversion rate of the catalyst reaches 46% and the vinyl chloride selectivity is 16%, which are much lower than the conversion rate and selectivity of Examples 1-5, indicating that Examples 1-5 have significant technical effects compared with Comparative Example 3.
[0084] Comparative Example 4
[0085] A. Dissolve magnesium chloride and aluminum chloride in 100 mL of boiling water at a molar ratio of 2 to prepare mixed salt solution I. The total amount of the two metal ions is 12 mmol·L -1 ; Dissolve NaOH in 100 mL of boiling water to a concentration of 24 mmol·L -1 Alkaline solution; CsB 12 H 12 Dissolve in 100 mL of boiling water to make a concentration of 12 mmol·L -1 Salt solution II. Under N2 atmosphere, the mixed salt solution I and the alkaline solution were simultaneously added dropwise to the salt solution II, and the pH of the solution was maintained at 8.5, and crystallized at 80°C for 96 hours; after the crystallization was completed, the mixture was washed, centrifuged and the supernatant was poured off, and then vacuum freeze-dried at a temperature of -50°C and a pressure of 0 MPa to obtain boron clusters located simultaneously in the layers and between the layers. 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs.
[0086] B. The B obtained in step A 12 H 12 / Mg 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in 50 mL of boiling water, and 2 mL of 2 mmol HNO3 solution was added dropwise under N2 atmosphere. After stirring, the supernatant was centrifuged and the Mg- ... 2+ Al 3+ -B 12 H 12 2- -Cl - -LDHs;
[0087] C. The boron cluster obtained in step B is intercalated into Mg 2+ Al3+ -B 12 H 12 2- -Cl - -LDHs precursor was evenly dispersed in 50mL of boiling water, and 2600μL of 50mmol·L -1 The Na2PdCl4 solution was stirred and centrifuged to remove the supernatant, and then freeze-dried at -50°C and 0 MPa to obtain aggregated B 12 H 12 -Pd n / Mg 2+ Al 3+ -LDHs nanoparticle catalyst, characterized by a Pd loading of 2.6 wt.% and a particle size of 2.5 nm, which far exceeds the interlayer spacing of hydrotalcite, resulting in the destruction of the hydrotalcite nanoreactor structure.
[0088] The catalyst prepared in Comparative Example 4 was used in the selective dechlorination reaction of trichloroethylene:
[0089] Weigh 0.3g of the above catalyst and 2g of quartz sand into a fixed bed reactor, introduce a mixed gas of H2 / C2HCl3=3 / 1, N2 as the balance gas and a total flow rate of 20-80mL / min, and test at 60-150°C. The reactor outlet gas is detected by gas chromatograph. The results are shown in Table 1. Figure 3 When the reaction temperature is 140°C, the trichloroethylene conversion rate of the catalyst reaches 68% and the ethylene selectivity is 29%; when the reaction temperature is 115°C, the trichloroethylene conversion rate is 25.9% and the vinyl chloride selectivity is 18%, which are much lower than the conversion rate and selectivity of Examples 1-5, indicating that Examples 1-5 have significant technical effects compared with Comparative Example 4.
Claims
1. A bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor, characterized in that: Indicated as B 12 H 12 -M1-Cl@X 2+ Y 3+ -LDHs, where M is a catalytically active and atomically dispersed metal, B 12 H 12 is the interlayer anion of the anchored active metal M; Cl is the interlayer anion adjacent to M1; X 2+ Y 3+ -LDHs is a hydrotalcite nanoreactor, wherein X is a divalent metal, Y is a high-valent metal, 2+ Y 3+ -LDHs interlayer spacing is 0.80-0.85nm, and the active metal M is in X 2+ Y 3+ -LDHs are dispersed atomically and stably between layers and are bound by adjacent Cl - The synergistic effect forms a bifunctional M-Cl active site.
2. The bifunctional catalyst based on the interlayer confinement effect of the hydrotalcite nanoreactor according to claim 1, characterized in that: M is at least one of Pd, Pt, Rh, and Ru, preferably at least one of Pd and Pt; preferably, the loading amount of M is 0.01 to 1.0 wt.%, more preferably 0.01 to 0.2 wt.%.
3. The bifunctional catalyst based on the interlayer confinement effect of the hydrotalcite nanoreactor according to claim 1 or 2, characterized in that: X is one or two of Mg, Zn, Cu, and Ni; Y is one of Al, Fe, Cr, Ti, and Zr.
4. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to any one of claims 1 to 3, characterized in that: The steps include: Step A, dissolving a divalent metal salt and a high-valent metal salt in boiling water to prepare a mixed salt solution I; dissolving an alkali in boiling water to prepare an alkali solution; dissolving a boron cluster compound in boiling water to prepare a salt solution II; Under an inert atmosphere, the mixed salt solution I and the alkaline solution are added to the salt solution II, and the pH of the solution is maintained at 8.5 to perform a crystallization reaction. After the crystallization is completed, the boron clusters are located in the layers and between the layers. 12 H 12 / X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs; Step B: B obtained in step A 12 H 12 / X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs were evenly dispersed in boiling water, and an oxidizing acid solution was added dropwise under an inert atmosphere. After stirring and centrifugation, the supernatant was poured off, and then dried to obtain a X-type product in which the boron clusters were located only between the layers. 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs precursor; Step C: inserting the boron cluster obtained in step B into the X 2+ Y 3+ -B 12 H 12 2- -Cl - -LDHs precursor is evenly dispersed in boiling water, and a metal salt solution with catalytic activity is added dropwise under an inert atmosphere. After stirring and centrifugation to remove the supernatant, the hydrotalcite nanoreactor with interlayer confinement effect and atomic-level dispersion is obtained after drying. 12 H 12 -M1-Cl@X 2+ Y 3+ -LDHs bifunctional catalysts.
5. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to claim 4, characterized in that: In step A, the total amount of metal ions in the divalent metal salt and the high-valent metal salt is 8 to 24 mmol·L -1 , preferably the molar ratio of the divalent metal salt to the high-valent metal salt is 2 to 5; In step A, the concentration of the alkaline solution is 16 to 48 mmol·L -1 , the concentration of salt solution II is 8~24mmol·L -1 .
6. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to claim 4, characterized in that: In step A, the crystallization reaction conditions are: crystallization at 70-90° C. for 72-120 h, preferably 84-100 h.
7. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to claim 4, characterized in that: In step A, the base is preferably one of NaOH and KOH; the boron cluster is preferably CsB 12 H 12 , Na2B 12 H 12 、K2B 12 H 12 Preferably, the mixed salt solution I and the alkaline solution are simultaneously added dropwise to the salt solution II; The boiled water in step A, step B and step C is preferably deionized water to remove the interference of carbon dioxide; The inert atmosphere in step A, step B and step C is preferably one of N2, Ar and He that does not contain CO2.
8. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to claim 4, characterized in that: In step B, the oxidizing acid is preferably one of HNO3, HNO2, HClO4, HClO2, and HClO, and more preferably one of HNO3 and HNO2; the concentration of the oxidizing acid solution is 1 to 5 mmol / L, preferably 1 to 2 mmol / L, and the amount used is 1 to 10 mL, preferably 1 to 5 mL.
9. The method for preparing a bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to any one of claims 4 to 8, characterized in that: The drying conditions in step A, step B and step C are preferably vacuum freeze drying at 0 to -60°C, preferably -50°C.
10. Use of the bifunctional catalyst based on the interlayer confinement effect of a hydrotalcite nanoreactor according to any one of claims 1 to 3 in hydrogenation and dechlorination reactions of organic chlorides.